Bioquímica quântica de interações ligante-proteína entre entre potenciais agentes anti maláricos e as enzimas DHODH e TyrRS do Plasmodium falciparum - Costa, Aranthya Hevelly de Lima (2023)
Malaria is a parasitic disease caused by unicellular protozoa of the genus Plasmodium and occurs in more than 90 countries, with the African and Asian continents predominating. The use of antimalarial drugs is critical for both treatment and prevention of the disease. However, the parasites began to develop resistance to antimalarials, making it more difficult to control the parasite. New therapeutic approaches are therefore needed to overcome the parasites' drug resistance and increase the effectiveness of drug therapy against the disease. The aim of this research is to characterize the relationships that affect the behavior of protein-ligand complexes of enzymes from Plasmodium falciparum. The first study aims to characterize dihydroorotate dehydrogenase (DHODH) and to present the energy levels of the enzyme in the complexes with wild-type PfDHODH, with ligands DSM483, DSM557, and DSM1, and with PfDHODH with the C276F mutation together with DMS1. In the second study, tyrosine RNAt synthetase (TyrRS) is examined, both in its wild-type PfTyrRS linked to ML901-Tyr and AMS-Tyr, and with the S234C mutation, again in complex with ML901-Tyr. Using the method of molecular fractionation with conjugated layers (MFCC), amino acid residues were partitioned to calculate individual interactions using the formalism DFT (Functional Density Theory). The study with PfDHODH enzyme revealed that amino acid residues Arg265, Cys184 and Phe188 were crucial for the interactions and exhibited significant interaction energies with the four complexes studied. Moreover, the energy value of the DSM1 inhibitor was not affected by the structural changes caused by the C276F mutation, demonstrating its ability to bind to the enzyme. Working with PfTyrRS, six important residues were found to be common to the three complexes. These residues include Asp61, Gln73, Gln192, Gln210, Met237, and Phe63, most of which play essential roles in ATP binding. This discovery provides a comprehensive understanding of the interaction between PfDHODH and PfTyrRS enzymes and their inhibitors. The information gathered in this study is proving to be relevant to the development of new drug therapies and could become a tool in exploring the design of new, more sophisticated and effective antimalarial drugs.